Adenosine Triphosphate Bioluminescence Assay versus Microbiological Swab Culture in the Evaluation of Surface Sanitation in a Pediatric Hospital in Romania - Tudorica (Sirmon) A; Bădițoiu LM; Anghel M; Laitin SMD; Muntean D; Kemper CA (Risk Management and Healthcare Policy)
Alexandra Tudorica (Sirmon),1,2 Luminița Mirela Bădițoiu,2,3 Mariana Anghel,3 Sorina Maria Denisa Laitin,3 Delia Muntean,2,4,5 Carmen Ana Kemper6 1Doctoral School, ‘Victor Babeș’ University of Medicine and Pharmacy, Timișoara, Romania; 2Department of Microbiology - Multidisciplinary Research Center on Antimicrobial Resistance, ‘Victor Babeș’ University of Medicine and Pharmacy, Timișoara, Romania; 3Department of Epidemiology, ‘Victor Babeș’ University of Medicine and Pharmacy, Timișoara, Romania; 4Department of Microbiology, ‘Victor Babeș’ University of Medicine and Pharmacy, Timișoara, Romania; 5Clinical Laboratory, ‘Pius Brînzeu’ Emergency Clinical County Hospital, Timișoara, Romania; 6Department of Prevention and Control of Healthcare Associated Infections, ‘Louis Țurcanu’ Children’s Emergency Clinical Hospital, Timișoara, RomaniaCorrespondence: Luminița Mirela Bădițoiu, Department of Epidemiology, “Victor Babes” University of Medicine and Pharmacy, Eftimie Murgu Square No. 2, Timisoara, 300041, Romania, Email baditoiu.luminita@umft.roPurpose: This study aimed to compare two rapid testing methods – Adenosine Triphosphate (ATP) quantification and the total Aerobic Colony Count (ACC) by bioluminescence assay with the standard method – microbiological swab culture. The goal was to determine the advantages and limitations of these rapid alternative tests in assessing the sanitary condition of hospital surfaces.Methods: A total of 88 samples were collected from various surfaces (stainless steel, metal, plastic, Tarkett, ceramic, glass, textile) in medical and surgical wards of a pediatric hospital. For each tested area, one sample underwent standard microbiological culture (25 cm²), and two adjacent samples (each 100 cm²) were analyzed using the ENSURE® TOUCH luminometer (Hygiena): one for ATP quantification (Ultrasnap) and one for ACC determination (Microsnap Total). Surfaces had been disinfected with commonly used agents—hydrogen peroxide, chlorinated products, or peracetic acid.Results: The Ultrasnap system identified 25 non-conforming samples; Microsnap Total found 13 non-conforming samples, while microbiological culture revealed one non-conforming sample and an additional 11 with low but detectable bacterial presence. The Ultrasnap method recorded a sensitivity of 100%, a specificity of 72.41% and an accuracy of 72.73%. In comparison, the Microsnap Total system showed higher specificity and accuracy (85.05% and 84.09%, respectively), but failed to identify the positive (non-conforming) test, resulting in a 0% positive predictive value.Conclusion: The study highlighted several advantages of rapid ATP tests, particularly their ease of use, their ability to provide results in just 10 seconds for Ultrasnap and approximately 7 hours for Microsnap Total, and their capacity to accurately identify well-sanitized surfaces. Additionally, Ultrasnap proved to be a sensitive indicator of residual organic matter, enhancing the capacity to distinguish between different sanitation levels and allowing cleaning and disinfection practices to be adjusted in real time, thereby reducing the risk of cross-transmission.Keywords: bioluminescence, ATP, disinfection, rapid assessment, hospital surfaces